2008
DOI: 10.1179/030192307x231865
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical analysis and optimisation for beam blank continuous casting

Abstract: The present work aims to simulate the solidification process during beam blank continuous casting, to determine the causes of defects, and to optimise the process parameters. A transient finite element model has been developed to compute the temperature and stress profile in beam blank continuous casting. It has been found that the surface temperature fluctuated greatly and that the equivalent stress and strain have their highest values at the flange tip and the web. By comparing the calculated values with met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…The simulation results in this study are basically the same as that of Chen et al [5]; thus, the simulation results are credible and the model is reasonable.…”
Section: Temperature Fieldsupporting
confidence: 79%
See 3 more Smart Citations
“…The simulation results in this study are basically the same as that of Chen et al [5]; thus, the simulation results are credible and the model is reasonable.…”
Section: Temperature Fieldsupporting
confidence: 79%
“…During the Chen et al [4] established a FEM coupled thermo-elastic-plastic model to compute the temperature and stress contours in the continuous casting of a steel beam blank and found that cracks were easily generated in the web and the flange tips. Chen et al [5] developed a 2D transient state model to simulate the stress and temperature distribution on the beam blank surface, discovering that high heat flow was the critical factor in surface crack formation on the web. They proposed an optimum water-spraying intensity, according to metallurgical criteria, to suppress surface cracking.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to a large energy-consuming and environmentally deteriorating condition, developing energy-saving materials and sustainable energy has aroused wide attention. Vanadium dioxide (VO 2 ) thin film is a first-order phase-changed material with superfast reaction speed that is near the critical temperature, 340 K [1,2]. This phase transformation is called a metal-insulator transition (MIT), and involves significant changes in electrical and optical characteristics.…”
Section: Introductionmentioning
confidence: 99%